VD_FINDINFO ML / 2015 / 8 vom 7. Januar 2015 - VD Tribunal cantonal (2015)
RECONNAISSANCE DE DETTE, MAINLEVÉE PROVISOIRE, TITRE DE MAINLEVÉE, SOLIDARITÉ PASSIVE | 143 al. 1 CO, 143 CO, 82 al. 1 LP, 82 LP